Management of sweet pepper diseases and growth promotion by Pseudomonas fluorescens and Trichoderma harzianum in mid Hills of central Himalayas, India - RANJIT SINGH*, SUNIL KUMAR, M.C. ARYA (Indian Phytopathology, 2010)
Growth attributes and disease management of damping off & powdery mildew under the influence of Pseudomonas fluorescens (PS) and Trichoderma harzianum (TC) separately as well as in combination were studied in Capsicum annuum var. grossum (cultivar Yolo Wonder) under protected environmental conditions. The experiment initiated by seed bio-priming (SB) with PS and TC and mixture of two (PS+TC) in equal quantity (W/W) for raising nursery followed by transplantation of seedlings in the pots with treatment combinations viz. Seed bio-priming (SB), SB+Root Dip (RD), SB+RD+Spray (SPR), SB+RD+ SPR + Drenching (DR) and control (C). Virgin garden soil (VGS) and vermi-compost (VC) added soil (VGSVC) with PS+TC combination had additive effect in enhancing the seedling length, fresh and dry weight of shoot and root. However, in case of virgin soil, C was more effective in enhancing the seedling length, where as the addition of vermi-compost in the soil gives PS an edge. Combined effect of PS+TC as seed bio-priming resulted in significant growth of seedling. After transplanting significant increase in plant height was observed only up to 45 days of transplanting. PS+TC combination induced plant growth and vigour in amended soil (VGSVC). SB+RD showed growth inducing effect up to crop maturity. PS+TC in combination with the treatment SB+RD+DR+SPR in VGSVC soil produced maximum number of fruits per plant. The disease incidence of damping off was 6.14% during the nursery stage only however the disease incidence of powdery mildew was severe (92.50 %) in control and least incidence (5.04-42.16 %) of powdery mildew was recorded in treatment SB+RD followed by SB+RD+SPR in VGS soil as compared to VGSVC soil. However, the spray treatment did not have positive impact in VGSVC soil, when used as medium for crop cultivation.